LIPUS combined with TFSC alleviates premature ovarian failure by promoting autophagy and inhibiting apoptosis - Weimei Zhou; Aixue Chen; Yongju Ye; Yuefang Ren; Jiali Lu; Feilan Xuan; Ruiying Jin (Taylor & Francis Group, 2023)
Objective Premature ovarian failure (POF), also known as primary ovarian insufficiency, is a major cause of infertility in female worldwide. Excessive apoptosis and impaired autophagy in ovarian granulosa cells are the main pathological mechanisms of POF. The total flavonoids from semen cuscutae (TFSC) are often used in the treatment of gynecological endocrine disorders. In addition, low intensity pulsed ultrasound (LIPUS) is report as an effective method to improve ovarian function. This study aims to investigate the protective effect of POF by the combined use of TFSC and LIPUS.Methods POF rats model and granulosa cell model were successfully induced by tripterygium glycosides and cyclophosphamide, respectively. After that, model rats and cells received TFSC plus LIPUS administration. Then ovarian histomorphology, senescence, estrus cycle, and serum sex hormone levels were detected in rats. Ovarian tissue and granulosa cells autophagy and apoptosis levels were also assessed.Results Disturbed sex hormone levels, atrophied and senescent ovaries, and abnormal estrous cycle were found in POF rats. Meanwhile, cell autophagy was inhibited and cell apoptosis was activated in POF ovarian tissue and granulosa cells. However, TFSC combined with LIPUS improved these changes, and this combination treatment exhibited synergistic effects. The abnormal expression of the cell apoptosis-, autophagy-, and PI3K/AKT/mTOR signaling pathway-related proteins were also improved by combination treatment.Conclusion The study found that the combination of TFSC and LIPUS can alleviate POF by modulating cell autophagy and apoptosis. The findings may provide a viable scientific basis for POF treatment.